Malaria Distribution in Riau Province, Indonesia: Descriptive Analysis of Health Profile Data 2018-2022 - Alvareza, Sitti; Ramadhani, Rivelin; Sakila; Selviana; Nurvima, Sitti (Journal of Epidemiology and Health Science, 2026)
Background: Malaria is a health problem that can lead to death. Malaria is still a significant public health problem in Riau Province, Indonesia. Factors such as environmental conditions, population density, and access to health services are thought to play a role in this distribution pattern. Objective: This study aims to describe the distribution of malaria in Riau Province. In particular, this study focuses on the identification of areas with the highest Malaria burden, analysis of trends in Malaria incidence from year to year, and exploration of factors that may influence the distribution pattern of this disease in Riau based on secondary data from the Riau Provincial Health Profile. Methods: This study used a quantitative descriptive design to analyze the distribution of Malaria in Riau Province. Secondary data was obtained from the annual report of the Riau Provincial Health Office which included Malaria case data, demographic characteristics, and geographical information. Data were processed and analyzed using descriptive statistical methods to describe the frequency, percentage, and trend of Malaria cases. Results: The results of the study showed significant variation in the distribution of Malaria cases in Riau Province. Some districts/cities have a higher incidence rate of Malaria compared to other regions. The trend of Malaria incidence from year to year shows fluctuations, with an increase in cases in certain years. Further analysis identified potential risk factors, such as areas with extensive forests, swampy areas, and limited access to health facilities, that contribute to the region's high rates of Malaria. Conclusion: The distribution of malaria in Riau Province is uneven, with some areas facing a heavier burden of the disease. Environmental factors, geographical accessibility, and socioeconomic conditions play an important role in influencing this distribution pattern. Malaria control efforts in Riau need to be focused on high-risk areas, with comprehensive intervention strategies including vector control, early diagnosis and treatment, and public awareness-raising. Further research is needed to deeply understand the dynamics of malaria transmission in Riau and to evaluate the effectiveness of ongoing control programs. Keywords: Malaria, Malaria Distribution, Risk Factors, Riau Province, Health Profile.